ENHANCING PHRASAL VERB ACQUISITION THROUGH TBLT IN SECONDARY ENGLISH CLASSROOMS - Nigina Ikromova (Bright Mind Publishing, 2025)
The integration of Task-Based Language Teaching (TBLT) to teach phrasal verbs to A2+ level students at a specialised secondary school for IT and English is examined in this paper. The study provides an organised TBLT lesson plan to enhance both receptive and productive abilities, highlights important resources, and explains the reasoning behind the use of phrasal verbs. It is based on a learner needs analysis and linguistic research. The reflection highlights the importance of combining learner-centred approaches, group projects, and explicit and implicit grammar instruction.